2018
DOI: 10.1101/280487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automated Adherent Cell Elimination by a High-Speed Laser Mediated by a Light-Responsive Polymer

Abstract: Conventional cell handling and sorting methods require manual dissociation, which decreases cell quality and quantity and is not well suited for monitoring applications. To purify adherent cultured cells, in situ cell purification technologies that are high throughput and can be utilized in an on-demand manner are expected. Previous demonstrations using direct laser-mediated cell elimination revealed only limited success in terms of their usability and throughput. Here, we developed a Laser-Induced, Light-resp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In addition, it was found that committed cells can be eliminated by a high‐speed laser irradiating specific areas of light‐responsive polymers (i.e. poly[(methylmethacrylate)‐co‐(Disperse Yellow 7 methacrylate)] layers) [26]. Alternatively, laminins of different isoforms promote different adhesion strength of various differentiated cell types.…”
Section: Methods To Purify Hpsc‐derived Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was found that committed cells can be eliminated by a high‐speed laser irradiating specific areas of light‐responsive polymers (i.e. poly[(methylmethacrylate)‐co‐(Disperse Yellow 7 methacrylate)] layers) [26]. Alternatively, laminins of different isoforms promote different adhesion strength of various differentiated cell types.…”
Section: Methods To Purify Hpsc‐derived Productsmentioning
confidence: 99%
“…Because cell/adhesive surface interactions are regulated upon differentiation, this has led to the development of novel biomaterials for the cell isolation of particular differentiated phenotype [25,26]. At the undifferentiated stage, iPSC colonies can be selectively detached from thermosensitive polymer (PNIPAAm (poly(N-isopropylacrylamide)), at low temperature (i.e.…”
Section: Separation Based On Cellular Biophysical Propertiesmentioning
confidence: 99%